ANALYSIS OF MEDAN CITY STRUCTURE BASED ON DISTRICT / CITY SPATIAL PLAN - Rini Kustiah Rahmadiana (PT. Radja Intercontinental Publishing, 2024)
This research aims to analyze and determine the suitability of determining the Regional Spatial Plan (RTRW) for Medan City for 2022-2042 in several sub-districts, as the center of economic growth in Medan City. Also to determine the level of geographic distribution of the availability of public facilities in each sub-district in Medan City. The research method used is a qualitative research method with a descriptive approach. The qualitative-descriptive method is a research procedure that produces descriptive data in the form of written or spoken words and observable behavior. The results of the research show that there are several sub-districts that do not comply with the Medan City RTRW projections for 2022 - 2042 in terms of urban spatial structure and there are also sub-districts whose designation is appropriate. This can be seen from the results of scalogram analysis and regional gravity analysis.